Partnership law in Malaysia - Latif, Samsar Kamar bin Hj. Ab. (International Law Book Services : Sole distributor, Golden Books Centre, 2003)
There is a great need for suitable law textbooks which can be used by students who are studying Malaysian partnership law in the universities and colleges in Malaysia.